A Molecular Investigation of Phytoplasma (Candidatus Phytoplasma) Infecting Arabic Jasmine (Jasminum sambac) in Iraq - Al-Kuwaiti, N. A. S.; Kareem, T.A.; Jameel, D. S. (Iraqi Journal of Science, 2023)
This study was conducted to investigate phytoplasma causing a virescence disease on Arabic jasmine Jasminum sambac based on microscopy and molecular approaches. Samples were collected from symptomatic Arabic jasmine plants grown in nurseries in Baghdad-Iraq. Specimens from infected plants were prepared and Dienes stained for light microscopy examination. Phytoplasma were detected in infected plants by polymerase chain reaction (PCR) using P1/P7 and SecAfor1/SecArev3 Candidatus Phytoplasma specific primer sets. Light microscopy test showed symptomatic Arabic jasmine plants were phytoplasms infected when phloem tissues were stained with a dark blue color. PCR test confirmed the symptomatic plants were phytoplasms infected when SecAfor1/SecArev3 primers could detect phytoplasms in tested samples. This primer set amplified the 831 bp DNA fragments of secA gene within phytoplasma genome from infected Arabic jasmine samples. Whereas, P1/P7 primer sets could not detect phytoplasms in tested samples. This study is the first molecular confirmation of the phytoplasma disease on Arabic jasmine in Baghdad-Iraq.